Why Do So Many Water Points Fail in Tanzania? An Empirical Analysis of Contributing Factors - Joseph, George (World Bank, Washington, DC, 2019)
According to the 2015 Tanzania Water Point Mapping data, about 29 percent of all water points are non-functional, out of which 20 percent failed within the first year. This paper analyzes the various factors which impact water point failure and measures the relative contributions of these determinants. The results indicate that water points managed by village committees had a much higher likelihood of failure than those managed by private operators or water authority. Factors that cannot be modified such as hydrogeological factors play a major role in determining water points failure during the first year after installation. However, management type as well as the type of pump and technology matter considerably more in the short and medium term.